FRAMING MEDIA ASING PADA PERISTIWA ERUPSI GUNUNG AGUNG - Kadek Wiramarta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Bali, as one of international tourism object has to maintain their positive image internationally. Realistically, news media have crucial role in influencing the image of a tourism object. In another side, tourism sector often faces crisis. This crisis is not always caused by human, but also by nature in form of natural disaster. This is what has been faced by Bali recently due to the eruption of Mount Agung. This research tries to comprehend on how international media present their news about Mount Agung eruption. To achieve this, framing analysis method proposed by Gamson and Mognliani (1987) was used. Based on the analysis, it has been found that international media tend to inform the news from the potential threat caused by Mount Agung eruption. This case mostly viewed geographically and historically. Besides that, the emerging effect caused by the eruption also becomes the focus of the news. Unfortunately, there is a little information about preparedness of related parties, disaster mitigation and the capability of related parties to handle the effect of Mount Agung eruption. This research hopefully can reflect the newsworthy issue and the framing used by international media in depicting the Mount Agung eruption. Keywords: Framing, International Media, Mount Agung Eruption